Here problem is not typed properly.
I think problem will be
"\\frac{dy}{dx}= \\frac{(2cos\u00b2x-sin\u00b2x)y\u00b2}{2cosx}"
"\\frac{dy}{y\u00b2}= \\frac{(2cos\u00b2x-sin\u00b2x)}{2cosx}dx"
Integrating both sides
"\\int\\frac{dy}{y\u00b2}= \\int\\frac{(2cos\u00b2x-sin\u00b2x)}{2cosx}dx"
"=> \\frac{dy}{y\u00b2}= \\frac{(3cos\u00b2x-1)}{2cosx}dx"
=> "\\int\\frac{dy}{y\u00b2}= \\int\\frac{3}{2}cosxdx-\\int\\frac{1}{2} secxdx"
=> "\\frac{-1}{y}= \\frac{3}{2}sinx-\\frac{1}{2} ln|secx+tanx| + C"
By given initial condition, when x = 0, y = -1
1 = 0 - 0 + C
So C = 1
So the particular solution is
"\\frac{-1}{y}= \\frac{3}{2}sinx-\\frac{1}{2} ln|secx+tanx| + 1"
=> 3ysinx - y ln|secx + tanx| + 2y + 2 = 0
Comments
Leave a comment